Pseudolaric acid B induces mitotic arrest and apoptosis in both 5-fluorouracil-sensitive and -resistant colorectal cancer cells. Issue 2 (28th December 2016) - Wen, Chuangyu; Chen, Junxiong; Zhang, Di; Wang, Huihui; Che, Jia; Qin, Qiyuan; He, Lu; Cai, Zerong; Lin, Mengmeng; Lou, Qiong; Huang, Lanlan; Chen, Daici; et al.
Abstract: 5-fluorouracil (5-FU)-based chemotherapy is the main chemotherapeutic approach for colorectal cancer (CRC) treatment. Because chemoresistance occurs frequently and significantly limits CRC therapies, a novel agent is needed. Pseudolaric acid B (PAB), a small molecule derived from the Chinese medicinal herb ''Tujinpi'', exhibits strong cytotoxic effects on a variety of cancers. However, the detailed mechanisms by which PAB inhibits CRC cell growth and its potential role in overcoming 5-FU resistance have not been well studied. In this study, we showed that PAB significantly inhibited the viability of various CRC cell lines but induced minor cytotoxicity in normal cells. Both the in vitro and in vivo results showed that PAB induced proliferation inhibition, mitotic arrest and subsequently caspase-dependent apoptosis in both 5-FU-sensitive and -resistant CRC cells. Moreover, PAB was shown to interfere with CRC cell mitotic spindle apparatus and activate the spindle assembly checkpoint. Finally, CDK1 activity was involved in PAB-induced mitotic arrest and apoptosis in CRC cells. Taken together, these data reveal that PAB induces CRC cell mitotic arrest followed by apoptosis and overcomes 5-FU resistance in vitro and in vivo, suggesting that PAB may be a potential agent for CRC treatment, particularly for 5-FU-resistant CRC. Highlights: PAB induces mitotic arrest followed by caspase-dependent apoptosis in CRC cells. PAB interferes with CRC cell mitotic spindle apparatus and activates the SAC. CDK1 activity is involved in PAB-induced mitotic arrest and apoptosis in CRC cells. PAB can circumvent 5-FU resistance in CRC cells.